2019
DOI: 10.3926/jiem.2735
|View full text |Cite
|
Sign up to set email alerts
|

Leadership profiles of successful project managers in Indonesia

Abstract: Purpose: This study examines the possible relationship between leadership competency and project performance within an Indonesia project-based organization setting. Four mediating variables are considered in the analysis: industry type, project complexity, project strategic value, and contract type.Design/methodology/approach: A cross-sectional quantitative survey was administered to empirically evaluate the theoretical model.  The targeted population was projected in Indonesia, and a snowball sampling method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…According to ICB-IMPA-2015 project manager's competencies has three aspects: intellectual, managerial, and emotional. A much more collaborated dissect review showed that all three leadership aspects (EQ, MQ, IQ,) responding separately to the success of the project [32] . Critical analysis, strategic viewpoint, and self-vision are comprised in the Intelligence Quotient (IQ).…”
Section: Project Manager's Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to ICB-IMPA-2015 project manager's competencies has three aspects: intellectual, managerial, and emotional. A much more collaborated dissect review showed that all three leadership aspects (EQ, MQ, IQ,) responding separately to the success of the project [32] . Critical analysis, strategic viewpoint, and self-vision are comprised in the Intelligence Quotient (IQ).…”
Section: Project Manager's Competenciesmentioning
confidence: 99%
“…The Management Quotient (MQ) comprises interconnection, resource management, team achievement, growth, and empowerment. Personality, openness to intuition, and governance is the aspects of emotional quotient (EQ) (inspiration and conscientiousness included) [32] . ICB-IMPA-2015 [13] proposed three aspects of project manager competencies.…”
Section: Project Manager's Competenciesmentioning
confidence: 99%
“…These variables were eventually excluded from the final theoretical model to maintain model's parsimony. Regarding task complexity, studies on complexity in other project domains such as project risk (Hartono, 2018) and project leadership (Hartono, Sulistyo & Umam, 2019) have found project complexity to affect the strength (i.e., weakness or strength) and sign (i.e., positive or negative) of the relationship between respective key predictors and project performance. Within project diversity research, however, this moderating effect seems to be negligible, as reported in a meta-analysis study by Horwitz and Horwitz (2007).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…From a complexity perspective, one can effectively understand and manage a megaproject (Flyvbjerg, Bruzelius & Rothengatter, 2003;Sato & Chagas Jr, 2014). This perspective can serve as a powerful analytical lens in terms of observing intricate problems that may stem from various project management settings, such as project failure (Ivory & Alderman, 2005), knowledge management (Hartono, Sulistyo, Chai & Indarti, 2019), stakeholders (Aaltonen & Kujala, 2016), leadership (Hartono, Sulistyo & Umam, 2019), tasks and scheduling (Ahn et al, 2017), team (Hsu, Weng, Cui & Rand, 2016), and project practice (Cooke-Davies, 2011). However, the literature review exhibits a limited focus in the context of megaproject studies.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has been deemed crucial to look into leadership aspects in megaproject management. Previous studies on regular project management have suggested that effective leadership depends on the project setting or attributes (e.g., the type of project (Müller & Turner, 2007), industry type, and project complexity (Hartono, Sulistyo & Umam, 2019). Similar strategies potentially apply in megaprojects, wherein project managers make choices according to the megaproject and its complexities (Sankaran, 2018).…”
Section: Introductionmentioning
confidence: 99%